2022
DOI: 10.3390/jpm12101685
|View full text |Cite
|
Sign up to set email alerts
|

IL-26 in the Lung and Its Role in COPD Inflammation

Abstract: IL-26 is a cytokine expressed by infiltrating pro-inflammatory IL-17-producing T cells in the tissues of patients with chronic lung inflammation. IL-26 induces the chemotactic response of human neutrophils to bacteria and other inflammatory stimuli. In recent years, the innovative properties of IL-26 have been described. Studies have shown that, as DNA is released from damaged cells, it binds to IL-26, which plays the role of a carrier molecule for extracellular DNA, further contributing to its binding to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
1
0
1
Order By: Relevance
“…Дослідження показали, що коли ДНК вивільняється з пошкоджених клітин, вона зв'язується з IL-26, який грає роль молекули-носія для позаклітинної ДНК, додатково сприяючи її зв'язуванню на місці запалення. Цей механізм дії вказує на те, що ІL-26 може служити як драйвером, так і стимулом запального процесу дихальних шляхів [29]. Аналіз експресії IL-26 при тяжкій формі БА як у периферичній крові, так і в індукованому мокротинні показав, що концентрації IL-26 вищі у сироватці крові та індукованому мокротинні пацієнтів з БА, ніж у групі контролю.…”
Section: особливості локального та системного запалення при бронхіаль...unclassified
“…Дослідження показали, що коли ДНК вивільняється з пошкоджених клітин, вона зв'язується з IL-26, який грає роль молекули-носія для позаклітинної ДНК, додатково сприяючи її зв'язуванню на місці запалення. Цей механізм дії вказує на те, що ІL-26 може служити як драйвером, так і стимулом запального процесу дихальних шляхів [29]. Аналіз експресії IL-26 при тяжкій формі БА як у периферичній крові, так і в індукованому мокротинні показав, що концентрації IL-26 вищі у сироватці крові та індукованому мокротинні пацієнтів з БА, ніж у групі контролю.…”
Section: особливості локального та системного запалення при бронхіаль...unclassified
“…Previous studies reported that IL-26 was found to associate with many proinflammatory cytokines, such as IL-6, IL-10, IL-17A, TNF-α, and mediated recruitment of T help cells [ 10 , 12 , 13 ]. Besides RA, recent studies reported that IL-26 was also found in many inflammatory lung diseases, such as asthma and chronic obstructive pulmonary disease (COPD) [ 14 ]. Even in the recent COVID-19 pandemic, IL-26 was regard as a marker of acute hyperinflammation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%